2017
DOI: 10.1111/medu.13347
|View full text |Cite
|
Sign up to set email alerts
|

Effective teaching of manual skills to physiotherapy students: a randomised clinical trial

Abstract: Peyton's four-step approach is more effective than the 'See one, do one' approach in skills laboratories aimed at developing physiotherapy student competence in C1-C2 passive mobilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 58 publications
1
53
0
1
Order By: Relevance
“…Traditionally, teaching of procedures employs a "See one, do one, teach one" approach and exemplifies the social cognition theory of learning that is best exemplified in hands-on-experiences and demonstrations. Over time, many teachers in areas of study including physiotherapy, have felt this type of learning can be improved through changes in teaching methods (Rossettini et al, 2017;Vozenilek et al, 2004;Mason & Strike, 2003). Furthermore, in our teaching centre, residents requested more exposure to Family Medicine procedures during the residency program, thus a gap was identified in their training that we wanted to address.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, teaching of procedures employs a "See one, do one, teach one" approach and exemplifies the social cognition theory of learning that is best exemplified in hands-on-experiences and demonstrations. Over time, many teachers in areas of study including physiotherapy, have felt this type of learning can be improved through changes in teaching methods (Rossettini et al, 2017;Vozenilek et al, 2004;Mason & Strike, 2003). Furthermore, in our teaching centre, residents requested more exposure to Family Medicine procedures during the residency program, thus a gap was identified in their training that we wanted to address.…”
Section: Discussionmentioning
confidence: 99%
“…The additional two steps might be assumed to be timeconsuming. However, in contrast to this, several authors have reported that not more time was required using Peyton's approach (Krautter et al, 2011;Rossettini et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Other authors have argued that recognising the effects of the instructions on the performance could be a valuable source of feedback and might improve metacognitive skills (Herrmann-Werner et al, 2013). In addition, Rossettini et al (2017) mentioned that Peyton's third step involves elements of mental practice. That is, the students have the possibility to develop a mental representation of the movement in absence of an active movement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations